SYSTEMATIC LITERATURE REVIEW: LITERASI KEUANGAN DAN GAYA HIDUP SEBAGAI DETERMINAN PENGELOLAN KEUANGAN IBU RUMAH TANGGA - M Arman Zarfani; Dwi Syawalansyah; Aulia Vina Febriana; Indrisetya Handayani; Irma Suryani (CV. KAMPUS AKADEMIK PUBLISING, 2026)
The role of housewives in managing family finances is a crucial factor in maintaining household economic stability. However, differences in financial literacy levels and increasingly consumptive lifestyles often affect the effectiveness of financial management. This study aims to systematically analyze the relationship between financial literacy and lifestyle as determinants of household financial management among housewives. The research employed a Systematic Literature Review (SLR) method following the PRISMA 2020 guidelines. Literature searches were conducted through Google Scholar and Scopus databases for publications between 2022 and 2025, using the keywords “financial literacy,” “lifestyle,” “financial management,” and “housewives.” A total of 35 articles were identified—22 from Google Scholar and 13 indexed in Scopus. After applying inclusion and exclusion criteria, 13 relevant studies were selected for in-depth analysis based on topic relevance, research methodology, and key findings. The results indicate that financial literacy positively and significantly influences the ability of housewives to plan, manage, and control family finances, whereas a consumptive lifestyle tends to reduce the quality of financial management. Furthermore, education level, income, and access to digital financial technology were identified as mediating variables that strengthen or weaken this relationship. This study contributes to the theoretical and practical understanding of the importance of enhancing financial literacy and managing lifestyle behaviors to promote household financial well-being in Indonesia.